Evaluating the benefits of co-curricular activities in a community service programme / Hairiani Abdul Hamid, Nor Diana Abd Rahman, Nur Diana Zamani, Zurina Omar and Yuanita FD Sidabutar - Abdul Hamid, Hairiani; Abd Rahman, Nor Diana; Zamani, Nur Diana; Omar, Zurina; FD Sidabutar, Yuanita (UiTM Cawangan Johor, 2024)
The purpose of this study was to investigate the benefits of-curricular activities for students enrolled in this module during semesters two and three at public institutions in Malaysia through community service programs. The advantages of extracurricular activities for students' knowledge, attitudes, academic performance, and skills in community service programs are the main emphasis of this study. 154 surveys were completed by students enrolled in a hvo-semester community service program. The four benefits of extracurricular activities are measured in this study using four sections with corresponding questions. The results of this study demonstrate the beneficial effects that student participation in community service projects has a positive and useful benefit towards student academic performance, enhancing student skills, improving student attitude, and improving student knowledge. Keywords: Co-curricular, Community service, Student academic, Student attitude, Student knowledge, Student skills